Rancang Bangun Trainer PLTS 50WP Untuk Menghidupkan Blower Kompor Konvensional - Darmawan, Heri; Ishak Allkadri, Syarif; Riatno, Riatno (entries, 2024)
Utilization of renewable energy, such as Solar Power Plants (PLTS), is becoming increasingly important in efforts to reduce dependence on fossil energy and reduce greenhouse gas emissions. The 50WP PLTS Trainer is designed to provide a practical and in-depth understanding of the installation and operation of small capacity PLTS. This trainer has a capacity of 50 watt peak (WP) and is specifically designed to turn on the blower on conventional stoves. The main components of this trainer include solar panels as the main energy source, a charging controller to regulate the current and voltage from the solar panels to the energy storage battery, and an inverter to convert direct current (DC) to alternating current (AC) needed to operate stove blower. Through the use of this trainer, users can learn the process of installing solar panels, designing battery charging systems, and setting up inverters to ensure compatibility and efficiency in operating conventional electrical devices. Thus, the 50WP PLTS trainer is an effective tool in supporting education and development of renewable energy technology in various environments. Keywords: Solar Power Plant (PLTS), PLTS Trainer, conventional stove, blower, solar energy.